Study on the Role of Local Government in Strengthening the Local Creative Economy Sector - Ali Zainal Abidin; Kenny Pradipta Montoya PP; Handy Nugraha (Universitas Muhammadiyah Ponorogo, 2022)
The creative economy’s GDP contribution continues to increase every year, relatively in accordance with the employment. By increasing the creative economy sector, it is expected that it will be able to solve problems in development and eliminate the economic dependence on natural resources. However, efforts to develop the creative economy still have a number of problems, which one of the main obstacles is the role of policy makers or the government. This research aims to further discuss the role of local government in supporting the development and the strengthening of the creative economy in Indonesia. This study applies a qualitative approach with the method of literature study, by obtaining secondary data from articles, journals related to the creative economy and local governments with a total of 51 papers. The data is collected from the Publish or Perish (PoP) application by using literature sources from Google Scholar and Scopus. For data analysis, this study applies content analysis through the stages of data collection, data reduction, data presentation and drawing conclusions. The validity of the data is tested by using source triangulation. The results of the study show that local governments have played an active role in the efforts to strengthen the creative economy sector. Yet, they still have a lot of homework to do in improving the quality of the creative economy sector.